I-Deals on the Retention of Human Talent in Health Networks in Satipo, Peru - Puente Yance, Hansel Renato (2024)
The objective of the research was to determine if there is an influence of i-deals on the retention of human talent in the health networks of Satipo, Peru. The study was carried out from a quantitative approach, with a correlational-non-experimental-translational design. A questionnaire was administered to 308 workers who negotiated one or more idiosyncratic agreements between December 2023 and February 2024. Using the structural equation model, it was obtained that the i-deals of work content (i-TC) and development (i-D) have a higher level of influence on the retention of human talent (p <0.05), generating a high commitment to the organization; based on the appropriate job assignment to employees according to technical and soft skills, and aligned with their personal interests. On the other hand, flexibility (i-F) and financial (i-FI) i-deals do not influence the retention of human talent, because the remuneration is not aligned with the required professional skills. It is concluded that for the public health sector, employees prefer to have autonomy in the way they perform their work, opportunities for professional specialization rather than financial incentives.